Tropicana Health & Fitness Centre (THFC) / Suria Saad ... [et al.] - Saad, Suria; Rasah, Zaharah; Ali, Sohana; Basir, Noraizura (Faculty of Office Management & Technology, 2002)
After discussing with all shareholders, we have decided to form a registered company under the name of Tropicana Health & Fitness Centre (T.H.F.C.). T.H.F.C. will provide services that focus on health and fitness activities.